Can Multiple Choice Exams Be Used to Assess Legal Reasoning? An Empirical Study of Law Student Performance and Attitudes - Danielle Bozin; Felicity Deane; James Duffy (Legal Education Review)
The purpose of this article is to examine whether legal reasoning skills can be appropriately assessed in a law degree, using multiple-choice question assessment. The use of multiple-choice assessment in university law schools is common, although not universally accepted as an effective pedagogical tool. In this article, both quantitative and qualitative empirical research methods have been adopted to examine whether the unique skill of legal reasoning is amenable to being tested through multiple-choice assessment. The position argued is that multiple-choice assessment, when properly constructed using identified guiding principles, is an efficient and effective way to assess legal reasoning abilities.